Pengaruh Kepemimpinan, Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi Pada Koperasi Unit Desa Pakis Kab. Malang) - Moh. Zaini; Abdul Kodir Djaelani; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study was used to determine how the influence of leadership, discipline and work motivation on employee performance partially at the Village Unit Cooperative (KUD) Pakis Kab.Malang. In this study, there are 4 variables used, namely the variables of leadership, discipline and work motivation are independent variables and employee performance which is the dependent variable. The research data collected was through a questionnaire using a Likert scale and the data analysis used was multiple linear regression analysis tested using SPSS. Sampling data using the Slovin formula with an error scale of 0.1, which is as many as 57 respondents. The results showed that leadership had a positive and significant effect on employee performance, work discipline had a positive effect on employee performance and work motivation had a positive and insignificant effect on employee performance. Keywords: Leadership, Discipline, Work Motivation, Employee Performance